Mobilitas Sosial pada Kelompok Zainichi Korean di Jepang - Wedayanti, Ni Putu Luhur; Dewi, Ni Made Andry Anita (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 4 No 1 (2022), 2022)
This study has a purpose to examine wether any social mobility occurred within Zainichi Korean in Japan. Zainichi Korean is a minority group that came to Japan since 1910 when Korean Peninsula was annexed by Japanese. Korean who came to Japan that time worked as daily worker in farming area, ship building, contruction site or other places. After World War II was ended, part of those Korean stayed remain in Japan, until this moment for fourth or fifth generatons. Decades ago, discrimination against Korean immigrants made it difficult for them to earn a decent living, as they struggled to find a decent work. They could only work as day laborers. However, due to various supporting factors such as opportunities and good cooperation, most of these Korean immigrants were able to own a Pachinko business, and even almost controlled the jewelry shop business in Osaka as the center of a settlement of the most Korean immigrants in Japan. This change shows the social mobility of Korean immigrants to a higher socioeconomic class. On the other hand, the factor that hinders the occurrence of mobility is the discriminatory attitude towards Zainichi Korean.